STUDENT’S STRATEGIES IN COPING WITH ENGLISH WRITING ANXIETY - Ikhsanudin; Meilsa Santri; Yanti Sri Rezeki (Journey: Journal of English Language and Pedagogy, 2022)
Investigating the causal factors, effects, and strategies to overcome writing anxiety is the aim of this research. A fifth semester student of English Education Study Program, Teacher Training and Education Faculty of Universitas Tanjungpura with high learning motivation was chosen as the participant of this research. A case study design was employed in this research by using semi-structured interview and document analysis as the method of data collection. The result of the data analysis indicated that the student experienced cognitive writing anxiety where she felt difficult in deciding a writing topic, choosing relevant vocabulary, and using appropriate grammar. Writing anxiety was caused by a high frequency of assignment, feeling lack of linguistics skill and vocabulary, and fear of being criticized by others. Based on the findings, it was revealed that the writing anxiety experienced by the participant brought a facilitative effect toward her writing performance which led her to take some efforts by managing several strategies to overcome the writing anxiety. It was reported that vocabulary checking, creating constructive surroundings to have writing practice, diary writing, and doing writing challenge were strategies she had used to overcome her writing anxiety.